Inhibitory properties underlying non-monotonic input-output relationship in low-frequency spherical bushy neurons of the gerbil - Kuenzel, Thomas; Nerlich, Jana; Wagner, Hermann; Rübsamen, Rudolf; Milenkovic, Ivan (Frontiers in Neural Circuits, 2015)
Spherical bushy cells (SBCs) of the anteroventral cochlear nucleus receive input from large excitatory auditory nerve terminals, the endbulbs of Held, and mixed glycinergic/GABAergic inhibitory inputs. The latter have sufficient potency to block action potential firing in vivo and in slice recordings. However, it is not clear how well the data from slice recordings match the inhibition in the intact brain and how it contributes to complex phenomena such as non-monotonic rate-level functions (RLF). Therefore, we determined the input-output relationship of a model SBC with simulated endbulb inputs and a dynamic inhibitory conductance constrained by recordings in brain slice preparations of hearing gerbils. Event arrival times from in vivo single-unit recordings in gerbils, where 70% of SBC showed non-monotonic RLF, were used as input for the model. Model output RLFs systematically changed from monotonic to non-monotonic shape with increasing strength of tonic inhibition. A limited range of inhibitory synaptic properties consistent with the slice data generated a good match between the model and recorded RLF. Moreover, tonic inhibition elevated the AP threshold and improved the temporal precision of output functions in a SBC model with phase-dependent input conductance. We conclude that activity-dependent, summating inhibition contributes to high temporal precision of SBC spiking by filtering out weak and poorly timed EPSCs. Moreover, inhibitory parameters determined in slice recordings provide a good estimate of inhibitory mechanisms apparently active in vivo.